2016
DOI: 10.1139/cjpp-2015-0446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum oxide (Al2O3) nanoparticles on ECG, myocardial inflammatory cytokines, redox state, and connexin 43 and lipid profile in rats: possible cardioprotective effect of gallic acid

Abstract: The objectives of present study were to examine the effects of aluminum oxide (Al2O3) nanoparticles on myocardial functions, electrical activities, morphology, inflammation, redox state, and myocardial expression of connexin 43 (Cx43) and the effect of gallic acid (GA) on these effects in a rat animal model. Forty male albino rats were divided into 4 equal groups: the control (normal) group; the Al2O3 group, rats received Al2O3 (30 mg·kg(-1), i.p.) daily for 14 days; the nano-alumina group, rats received nano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 37 publications
2
26
0
1
Order By: Relevance
“…Others works have showed that gallic acid could suppress the release of pro-inflammatory cytokine interleukin (IL)-6, IL-31-and IL-33 and pretreatment with GA ameliorates myocardial injury induced by nano-alumina, probably through its hypolipidemic, anti-inflammatory, and antioxidant effects. 49,50) Previous studies using rutin (50, 70 mg/kg) in the treatment of hepatotoxicity CCl 4 -induced showed similar results, with a significant reduction in the amounts of serum enzymes ALT, AST and GGT hepatic, lipid peroxidation and an increase in liver GSH. 13) Tirkey et al 51) showed similar results using hesperidin at doses of 100 and 200 mg/kg.…”
Section: Discussionsupporting
confidence: 52%
“…Others works have showed that gallic acid could suppress the release of pro-inflammatory cytokine interleukin (IL)-6, IL-31-and IL-33 and pretreatment with GA ameliorates myocardial injury induced by nano-alumina, probably through its hypolipidemic, anti-inflammatory, and antioxidant effects. 49,50) Previous studies using rutin (50, 70 mg/kg) in the treatment of hepatotoxicity CCl 4 -induced showed similar results, with a significant reduction in the amounts of serum enzymes ALT, AST and GGT hepatic, lipid peroxidation and an increase in liver GSH. 13) Tirkey et al 51) showed similar results using hesperidin at doses of 100 and 200 mg/kg.…”
Section: Discussionsupporting
confidence: 52%
“…Supplementation of gallic acid in several cardiotoxicity models have shown cardioprotective and antiinflammatory properties. Gallic acid was able to limit cardiac injury, improve lipid profile and downregulate cardiac inflammatory markers such as NO and TNF-α, although no improvement was seen in circulating NO and TNF-α level (El-Hussainy et al, 2016). Similarly, treatment with gallic acid mitigated diazinon induced cardiorenal toxicity by reducing cardiac and renal NO, besides alleviating oxidative stress and improving the hematological parameters of rats (Ajibade et al, 2016).…”
Section: Gallic Acidmentioning
confidence: 96%
“…Antioxidant effects of gallic acid mitigated diazinone-induced cardiovascular dysfunction in a rat animal model 28 and cyclophosphamide-induced cardiorenal dysfunction 29 . Gallic acid was reported to have cardioprotective effects following exposure to various substances such as aluminum oxide 30 , lindane 31 , and isoproterenol 32 .…”
Section: Discussionmentioning
confidence: 99%